2017
DOI: 10.11622/smedj.2017063
|View full text |Cite
|
Sign up to set email alerts
|

Basic Cardiac Life Support: 2016 Singapore Guidelines

Abstract: Basic Cardiac Life Support (BCLS) or cardiopulmonary resuscitation (CPR) refers to the skills required (without use of equipment) in the resuscitation of cardiac arrest individuals. On recognising cardiac arrest, chest compressions should be initiated. Good quality compressions are with arms extended, elbows locked, shoulders directly over the casualty's chest and heel of the palm on the lower half of the sternum. The rescuer pushes hard and fast, compressing 4-6 cm deep for adults at 100-120 compressions per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 32 publications
0
19
0
4
Order By: Relevance
“…A study by Gonzaga et al 9 found that 86% of the interviewed dentists had received information about CPR; however most of them had not received practical training for cardiopulmonary resuscitation. In recent years several publications have highlighted the deficiencies in CPR quality, both out of hospital and in hospital, which have partly been addressed in the newest BLS guidlines 9,10. CPR is controlled by guidelines developed by certain associations such as American heart association 11 and some other associations in Europe 12 Singapore 13 Australia, and New Zealand.…”
Section: Reddy Et Almentioning
confidence: 99%
“…A study by Gonzaga et al 9 found that 86% of the interviewed dentists had received information about CPR; however most of them had not received practical training for cardiopulmonary resuscitation. In recent years several publications have highlighted the deficiencies in CPR quality, both out of hospital and in hospital, which have partly been addressed in the newest BLS guidlines 9,10. CPR is controlled by guidelines developed by certain associations such as American heart association 11 and some other associations in Europe 12 Singapore 13 Australia, and New Zealand.…”
Section: Reddy Et Almentioning
confidence: 99%
“…This is addressed in Lim et al's Basic Cardiac Life Support: 2016 Singapore Guidelines. (35) An unresponsive casualty who is breathing normally should be positioned in a lateral, side-lying recovery position as opposed to the supine position. This position involves extending one of the arms of the person above the head and rolling the body to the side so that the person's head rests on the extended arm.…”
Section: Medicalmentioning
confidence: 99%
“…The fi rst of these guidelines was published in 2001, (6)(7)(8) Treatment Recommendations (CoSTR) was followed by the release of the 2006 Singapore Resuscitation Guidelines. (9) The fi rst full set of national resuscitation guidelines (10)(11)(12)(13) for the country was published in 2011, after the release of the ILCOR 2010 CoSTR documents. In addition to national resuscitation guidelines, the NRC has also released guidelines and position statements on special areas of concern, especially on compression-only CPR (14) and CPR+AED facility management programmes.…”
Section: National Resuscitation Guidelinesmentioning
confidence: 99%